Kajian Molecular Docking Senyawa Quercetin dari Buah Terong Pokak (Solanum torwum Swartz) sebagai Antiinflamasi pada Protein Tumor Necrosis Factor-α (TNF-α) - Lusi Thenios; Noer Komari (Jurnal Natural Scientiae, 2022)
Quercetin is a polyphenolic flavonoid with potential chemopreventive activity. Quercetin is a chemical compound found in Solanum torvum Sw fruit. Quercetin is one of the compounds that are considered to have anti-inflammatory effects. Inflammation is a localized protective response elicited by tissue damage caused by physical trauma, damaging chemicals, or microbiology. Tumor Necrosis Factor-α (TNF-α) is a proinflammatory cytokine that functions in mediating the innate immune response. Irregular production of cytokines can lead to various immunopathological conditions, including auto-inflammatory, autoimmune, and cancer-causing diseases. This study aims to determine the potential of quercetin compounds derived from turkey berry (Solanum torvum Sw.) which have the potential as anti-inflammatory drugs with parameters such as ∆G, the interaction of residues on TNF-α protein (PDB ID: 6X85) with molecular docking, and pharmacophore studies using Lipinski, pkCSM, and SwissADME filters. The molecular docking simulation results showed that the quercetin compound had a ∆G value of -8.55 kcal/mol and had amino acid residue interactions in the form of ILE155; TYR59; GLY121; TYR119; GLN61; TYR151; VAL123; LEU157; ILE58; GLY122; SER60; LEU120; LEU157. Quercetin has the potential as an anti-inflammatory drug on TNF- α protein with an LD50 value of 2.471; bioavailability value of 0.55; does not have hepatotoxicity and skin sensitization properties and has passed the Lipinski test.